Enhancing Propagation Length of Surface Plasmon Polaritons by Using Metallic Double-Layer Structure - Manh Hoang Chu; Minh-Tuan Trinh (IEEE Photonics Journal)
In this paper, we propose to use a wedge-shaped plasmonic waveguide with a metallic double-layer structure for improving the propagation length of surface plasmon polaritons. The wedge silicon waveguide is covered by a first layer of Ag and by a second layer of Au outermost in which the former has a good lightwave guiding property but unstable to the operating medium and the latter is more stable to the operating medium. Numerically investigated results show that the propagation length of surface plasmon polaritons using the Au/Ag double-layer structure with an appropriate thickness of the Au covering layer can be increased by a factor of 2.5 compared to that of using the only Au metallic structure at the same propagation mode area. The advantage of the proposed metallic double-layer structure is also preserved in hybrid plasmonic waveguides.